Comprehensive care postabortion, in maternal perinatal institute specialized. 1995-2004 - Mascaro Sánchez, Pedro (2015)
OBJECTIVES. To determine the experience in ambulatory abortion care. DESIGN. Clinical retrospective study. SETTING. Instituto Especializado Materno Perinatal (IEMP), Lima, Peru, a teaching hospital. PARTICIPANTS. Women with less than 12-week abortions. INTERVENTIONS. We analyzed abortions attended at our institution, in the period 1995-2004. We compared instrumental dilatation and curettage versus intrauterine manual aspiration (IUMA) as well as diagnosis justifying the surgical intervention and complications. MAIN OUTCOME MEASURES. Abortion surgical interventions and complications, counsel ing and costs. RESULTS. Between 1995 and 2004, 58 757 abortions were attended at IEMP, 19 295 (32,8%) of them ambulatory; in year 2004, 47,3% were ambulatory. Intrauterine manual aspiration was the most used method (92,1%); the few complications (1,87%) included insufficient IUMA, hematometra, post abortion endometritis and pelvic inflammatory disease. Paracervical analgesia with lidocaine or intravenous petidine was used. Patients remained in the emergency room about 2 to 4 hours and the ambulatory abortion care cost was amply advantageous in relation to hospitalized care of abortion. Family planning counseling was done in 81,1% of cases and 50,4% was discharged with a contraceptive method. CoNCLUSIONS. At IEMP the classical abortion care with hospitalization has become ambulatory, done in the emergency room. This model proposed by the Peruvian Health Ministry and Pathfinder for integral post abortion care has been validated and gradually institutionalized; the project concluded in year 2002 and its application is in force, with advantages for both patient and institution.